Youtube sebagai media dakwah: Analisis semiotika animasi anak ‘adab sebelum ilmu' pada Youtube channel riko the series - Sutisna; Aprilita, Ananda Laela; Lisnawati, Santi (KOMUNIKA, 2023)
Instagram is one of the popular social media because it displays a variety of interesting features that can be used by its users to preach. The method of preaching through Instagram has attracted a lot of attention from various circles, especially teenagers. One of the preachers who consistently preaches on Instagram is Ustadz Hilman Fauzi in his Instagram account, namely @ahilmanfauzi. This study aims to determine the relationship between the behavior of watching Instagram @ahilmanfauzi and the behavior of monotheism students of the 2018 Faculty of Islamic Religion, Ibn Khaldun University, Bogor. This study uses a quantitative approach with data collection techniques using a questionnaire. The population is 336 students, the sample calculation uses the Slovin formula and the results are 80 students. The data analysis technique used hypothesis testing. The results of this study are Ha is accepted because the correlation significance value is 0.000 <0.05 and the calculated R value is 0.590 > R table 0.220 so it can be said that there is a positive relationship, meaning that the increasing viewing behavior will increase the monotheistic behavior of students of the Islamic religious faculty. 2018 Ibn Khaldun University Bogor. The limitation in this study lies in that there are still many students who know but do not follow the @ahilmanfauzi Instagram account so that researchers have difficulty in finding respondents. The results of this study are used as input for students to watch something positive which will result in positive behavior.